(untitled) (Ozone Therapy Global Journal, 2022)
The prospective observational study presented at this time aims to demonstrate the efficacy and safety of growth factor concentrate combined with ozone-induced mesenchymal stem cells. The effect that favors the process of cicatrization, regeneration, or healing of damaged tissue is applied either as an outpatient or as a complement to a surgical technique. To this end, this study included a sample of 32 patients from the private practice, from February 2021 to February 2022 who presented pain, difficulty in walking. Under the usual asepsis and antisepsis standards, all individuals were implanted with concentrated platelet growth factors combined with ozone-induced mesenchymal stem cells, prior informed consent under ultrasound and fluoroscopic navigation. The patient’s evolution was monitored by monitoring clinical and radiological symptoms based on the visual analog pain scale. (Eva 2,43) at 15 days; (Eva 1,8) per month; (Eva 1,5) at three months and (Eva 1,0) at 6 months with Rx control. It should be noted that the visual analog scale evidenced significant improvement of (p <0.005), concerning initial condition and MRI showed recovery of the treated hip cartilage, consequently, the results described demonstrate the efficacy and safety of the use of concentrates of platelet growth factors combined with ozone-induced mesenchymal stem cells in this type of pathology, since no adverse effects have been reported, in the use of this treatment.